Clinical utility of reflex testing using focused next-generation sequencing for management of patients with advanced lung adenocarcinoma. Issue 12 (18th September 2018) - Miller, Tyler E; Yang, Michael; Bajor, David; Friedman, Judah D; Chang, Richard Y C; Dowlati, Afshin; Willis, Joseph E; Sadri, Navid
Abstract : Aims: The growing number of genomically targeted therapies has made genomic testing an important part of the care for patients with non-small cell lung cancer. However, limited tissue availability, cost and long turnaround times can create barriers to efficient genomic testing and subsequent treatment. Effective approaches to reduce these barriers are needed. Methods: 302 advanced lung adenocarcinomas from consecutive patients seen at University Hospitals Cleveland Medical Center (UHCMC) were tested inhouse using a hybrid DNA/RNA next-generation sequencing (NGS) panel. Sample testing was reflexed from pathology for all stage III or IV tumours. Genomic alterations were tiered according to their clinical relevance and reported with guideline-recommended therapies. Clinical implications of genomic testing results were assessed by manual chart review. Results: With a sample cohort consisting of 64% biopsies, 16% excisions/resections and 20% fine needle aspirations, the assay was reliable with a 95% success rate. The average turnaround time from receipt of unstained formalin-fixed paraffin embedded slides to reporting was 4.8±2.1 days, half of the recommended 10 days and similar to single-gene testing. Alterations with Food and Drug Administration-approved or the National Cancer Center Network guideline-recommended targeted therapies were found in 18% of cases. Within this group, 60% of patients went on genomically driven therapies. Conclusions: We found our reflexed inhouse NGS assay to be reliable, cost-effective and efficient. Incorporation of reflex testing with our NGS assay led to an expansion of successful genomic profiling for all guideline-recommended alterations, and by including an expanded number of alterations within our panel we obtained clinically useful information outside the guidelines without changing cost or efficiency. This approach has enabled UHCMC clinicians to efficiently initiate genomically driven therapies for patients with lung adenocarcinoma.